PELATIHAN STRATEGI CORPORATE BRANDING PENGUSAHA MELALUI KONTEN - Detya Wiryany; Rizky Surya Tawaqal; arie hendra saputro (Politeknik Negeri Sriwijaya, 2023)
MSME actors have quite big challenges to survive and grow with the current state of affairs,as well as increasingly fierce competition in the business and creative world. The current conditionsare also a challenge that is not easy during this pandemic, MSMEs are increasingly squeezed by thecondition of declining consumer buying interest in MSME products. MSMEs today must be digitallyliterate, this is to accelerate brand growth so that it is easily recognized by the public. According todata from